Positive allosteric GABAA receptor modulation counteracts lipotoxicity-induced gene expression changes in hepatocytes in vitro - Rohbeck, Elisabeth; Niersmann, Corinna; Köhrer, Karl; Wachtmeister, Thorsten; Roden, Michael; Eckel, Jürgen; Romacho, Tania (Frontiers in Physiology, 2023)
We have previously shown that the novel positive allosteric modulator of the GABAA receptor, HK4, exerts hepatoprotective effects against lipotoxicity-induced apoptosis, DNA damage, in-flammation and ER stress in vitro. This might be mediated by downregulated phosphorylation of the transcription factors NF-κB and STAT3. The current study aimed to investigate the effect of HK4 on lipotoxicity-induced hepatocyte injury at the transcriptional level. HepG2 cells were treated with palmitate (200 μM) in the presence or absence of HK4 (10 μM) for 7 h. Total RNA was isolated and the expression profiles of mRNAs were assessed. Differentially expressed genes were identified and subjected to the DAVID database and Ingenuity Pathway Analysis software for functional and pathway analysis, all under appropriate statistical testing. Transcriptomic analysis showed substantial modifications in gene expression in response to palmitate as lipotoxic stimulus with 1457 differentially expressed genes affecting lipid metabolism, oxidative phosphorylation, apoptosis, oxidative and ER stress among others. HK4 preincubation resulted in the prevention of palmitate-induced dysregulation by restoring initial gene expression pattern of untreated hepatocytes comprising 456 genes. Out of the 456 genes, 342 genes were upregulated and 114 downregulated by HK4. Enriched pathways analysis of those genes by Ingenuity Pathway Analysis, pointed towards oxidative phosphorylation, mitochondrial dysregulation, protein ubiqui-tination, apoptosis, and cell cycle regulation as affected pathways. These pathways are regulated by the key upstream regulators TP53, KDM5B, DDX5, CAB39L and SYVN1, which orchestrate the metabolic and oxidative stress responses including modulation of DNA repair and degradation of ER stress-induced misfolded proteins in the presence or absence of HK4. We conclude that HK4 specifically targets mitochondrial respiration, protein ubiquitination, apopto-sis and cell cycle. This not only helps to counteract lipotoxic hepatocellular injury through modifica-tion of gene expression, but - by targeting transcription factors responsible for DNA repair, cell cy-cle progression and ER stress - might even prevent lipotoxic mechanisms. These findings suggest that HK4 has a great potential for the treatment of non-alcoholic fatty liver disease (NAFLD).